Mechanics and Strength of Materials - da Silva, Vitor Dias (Springer Berlin Heidelberg : Imprint: Springer, 2006)
This treatise contains topics on Solid Mechanics, the Theory of Slender Members and an Introduction to the Theory of Structures, usually taught in the disciplines of Strength of Materials of most Engineering courses, such as Civil, Mechanical and Aeronautical Engineering. In relation to the most widely known treatises on Mechanics and Strength of Materials, a greater scientific exactness and an extra emphasis on the theoretical justification of the topics explained may be stressed. Axioms and non-demonstrated simplifying hypotheses, which are common in this kind of book, are avoided. The depth of the explanation is at an intermediate level between those works and treatises based on a mathematical approach to the Theory of Elasticity and Continuum Mechanics. However, the topics are always introduced from a physical point of view, which is fundamental for an Engineer, and are anchored on over 300 figures of high graphical quality.